Rational Pharmacotherapy of Acute Viral Tonsillopharyngitis in Children - H.O. Lezhenko; O.Ye. Pashkova (Zaslavsky O.Yu., 2014)
This paper presents data on the etiology of acute tonsillopharyngitis, differential diagnostic criteria for viral and bacterial tonsillopharyngitis. The evaluation of the dynamics of clinical symptoms in acute viral tonsillopharyngitis has been carried out when using Tantum Verde® (benzydamine hydrochloride). High efficiency and safety of benzydamine hydrochloride use in children has been proved.